Adenosine Deaminase as Inflammatory Marker in Type II Diabetes Mellitus - Yadav, Sushil; Bansal, Megha; Kumar, Pradeep; Sharma, Preeti (International Journal of Integrated Health Sciences, 2023)
Objective: To evaluate the enzymatic activity of Adenosine Deaminase in type II diabetes mellitus (T2DM).Methods: This study was conducted on 60 clinically diagnosed type II diabetes mellitus patients, with 60 healthy subjects as the control group. Subjects were enrolled in the study only after their written consent was obtained. The inclusion of diabetes mellitus cases (DM) was conducted as per the WHO guidelines. Estimation of enzymatic activity of serum ADA was performed by Kinetic method using a commercial kit.Result: The observed serum ADA activity in DM patients was 48.34 ± 21.05 U/L, which was significantly higher in comparison to healthy controls (25.02 ± 5.78 U/L). The serum activity raised in about 80% of patients and they had higher values above the reference activity of 30 U/L. The increased activity of ADA among the diabetic subjects indicates inflammatory changes in these individuals.Conclusion: It is possible that in the coming years, a new therapeutic strategy based on anti-inflammatory properties with beneficial effects on diabetic complications can be translated into real clinical treatments.